SPORTS ALTERNATIFS : UN ABORDAGE CRITIQUE EMANCIPATÓRIA DANS LE CONTEXTE SCOLAIRE (Fiep Bulletin - online, 2014)
Understanding the work of it disciplines of Physical Education as the moment where the pupils understand its proper corporeidade, this work has for objective to prove that the insertion of the practical one of alternative sports in the lessons of this disciplines makes possible the change of position and behavior of the pupils and mobilizes the interest in the practical one and lives deeply corporal. The work was developed in disciplines them of Supervised Period of training: Practical research of the Pedagogical and Practical Professor - Integrated Projects, having as research field the Basic School Alberto Professor Werner, which belongs to the Municipal Net of Education of Itajaí/SC. With the intention of better understanding the research process, the work, it had as base the principles of the qualitative research, being used for collection of the data instruments as: informal interviews, participant comment, guided by daily of field and stages of planned monitorias. They had been citizens of the research, the administrative team of the school, the professor of Physical Education and the pupils registered the groups of 5ª 8ª series of Basic Ensino. The research occurred in the period of March á June of 2006 with the intention of problematizar the teaching action to identify problematic, a discutiz one it and to consider metodológicas alternatives, using as education object alternative sports. The organization of the Plans of Action for the interventions in the stages of monitoria, was made possible by the previous moments of participant comment and informal interviews, favoring the reflections of the context of the lessons of Physical Education and lives deeply with a differentiated methodology. The experience of the monitorias made possible the joint practical theory, new reflections and reorganization of the following monitorias. The analysis of the collected data contributed for the understanding of the paper of the professor as mediating in the process of position changes and behavior of the pupils related to its you live deeply corporal and showed to the importance of the use of the alternative sports as resources didactic metodológico.
Keywords: Pertaining to school Physical Education; Alternative Sports; Practical Metodológicas